1990
DOI: 10.1007/bf01101704
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor changes in brain synaptic membranes from human alcoholics

Abstract: Brains from human alcoholics and non-alcoholics were obtained shortly after death. The hippocampus was dissected, homogenized, and processed for the isolation of a synaptic membrane-enriched fraction and the study of L-[3H]glutamic acid and 3-((+-)-2-carboxypiperazin-4-yl)-[1,2(3H)propyl-1-phosphonic acid ([3H]CPP) binding sites. The pharmacological characteristics of L-[3H]glutamic acid binding to synaptic membranes isolated from hippocampus corresponded to the labeling of a mixture of N-methyl-D-aspartate (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 32 publications
0
22
1
2
Order By: Relevance
“…Long-term alcohol exposure increases both numbers of postsynaptic NMDA receptors and their sensitivity (38), but the postsynaptic intracellular calcium level remains constant and NO production is not altered (39,40). Our results showed that brain NO x levels of mice exposed to ethanol for 4 weeks did not differ from those in controls, but those of mice exposed for 12 weeks had decreased significantly.…”
Section: Figcontrasting
confidence: 60%
“…Long-term alcohol exposure increases both numbers of postsynaptic NMDA receptors and their sensitivity (38), but the postsynaptic intracellular calcium level remains constant and NO production is not altered (39,40). Our results showed that brain NO x levels of mice exposed to ethanol for 4 weeks did not differ from those in controls, but those of mice exposed for 12 weeks had decreased significantly.…”
Section: Figcontrasting
confidence: 60%
“…One of the earliest findings suggesting glutamate involvement was the finding that [ 3 H]glutamate binding is increased in the human hippocampus of alcoholics (67). Although the subtype of the glutamate receptor involved is not clear, this is consistent with increased glutamate receptor density and sensitivity.…”
Section: Excitotoxicitymentioning
confidence: 89%
“…Chronic exposure to ethanol can sensitize neurons to the excitotoxic effect of NMDA receptor activation due to the upregulation of the NMDA receptors [13,22,27,35,36,51,52,126,133,138]. Human postmortem ligand binding studies demonstrate an increase of NMDA receptor density [32] and affinity [82]. Consistent with these findings, animals develop withdrawal seizures after withdrawal have increased [ 3 H]-MK-801 binding sites in entorhinal cortex and hippocampus, compared to those in which withdrawal seizures are not observed [137].…”
Section: Pathophysiological Studiesmentioning
confidence: 99%